2014
DOI: 10.1002/ejic.201402005
|View full text |Cite
|
Sign up to set email alerts
|

Star‐Shaped Quaternary Alkylammonium Polyhedral Oligomeric Silsesquioxane Ionic Liquids

Abstract: New star‐shaped quaternary ammonium (QA) polyhedral oligomeric silsesquioxane (POSS) salts based on octakis(tetraalkylammonium) POSS cations bearing alkyl chains of different length (methyl, n‐butyl, and n‐octyl) and differently polarizable anions [iodide, bis(trifluoromethylsulfonyl)imide, and ibuprofen] have been synthesized and characterized. Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) investigations show that the nature of the cation plays a key role in determining the ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 41 publications
0
21
0
5
Order By: Relevance
“…148 The 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 The aforementioned star-like oligo(ionic liquid)s are inorganic-organic compounds in terms of their global chemical composition. The reports on fully organic star-like poly(ionic liquid)s in the literature are scarce.…”
Section: Star Poly-and Oligo(ionic Liquid) Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…148 The 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 The aforementioned star-like oligo(ionic liquid)s are inorganic-organic compounds in terms of their global chemical composition. The reports on fully organic star-like poly(ionic liquid)s in the literature are scarce.…”
Section: Star Poly-and Oligo(ionic Liquid) Materialsmentioning
confidence: 99%
“…147,148,149,150,151,152,153,154,155,156,157,158,159,160 Based on the range of molecular masses involved, these compounds can be regarded as OIL compounds. Their molecular weight depends on the length of the spacer and the type of the ionic group and starts from 1338 g/mol for derivatives with one arm 147 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 temperature of 172°C.…”
Section: Star Poly-and Oligo(ionic Liquid) Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of our studies regarding the synthesis and properties of POSS tetraalkylammonium (POSS-QAs) ILs [16][17][18], we have found that ''pendant functionalized'' monosubstituted R 7 -POSS-NMe 3 + (R = isooctyl) ILs, in contrast with conventional ones, display a chemical behavior determined by the bulky amphiphilic cation. This, being characterized by a hydrophobic organic corona on the ''OASiAO'' siloxane core and a hydrophilic ammonium pendant group, exhibits a cationic surfactant behavior in organic solvents and a remarkable extraction capability of various polyanions from aqueous solution.…”
Section: Introductionmentioning
confidence: 98%
“…Ionic liquids (ILs), which have been recognized as a novel class of synthetic materials, have melting points below 100 °C [1,2,3]. With increasing demand for advanced materials, the development of novel ILs has been increasingly explored due to their unique properties [4], which include high ionic conductivity [5], high thermal stability, non-flammability, negligible vapor pressure, and a wide electrochemical stability window [6,7]. Due to the above advantages, ILs have been applied as functional materials in many chemical and industrial fields including fuel cells and lithium batteries [8], particular as catalysis solvents, capacitors, and electrochemical sensors [3].…”
Section: Introductionmentioning
confidence: 99%